Role of Interfacial Bonding in Tribochemical Wear - Luo, Chunsheng; Jiang, Yilong; Liu, Yangqin; Wang, Yang; Sun, Junhui; Qian, Linmao; Chen, Lei (Frontiers in Chemistry, 2022)
Tribochemical wear of contact materials is an important issue in science and engineering. Understanding the mechanisms of tribochemical wear at atomic-scale are favorable to avoid device failure, improve the durability of materials, and even achieve the ultra-precision manufacturing. Hence, this paper reviews some of the latest developments of tribochemical wear of typical materials at the atomic-scale that commonly used as solid lubricants, tribo-elements, or structural materials of micro-electromechanical devices, focusing on their universal mechanisms based on the studies from experiments and numerical simulations. Particular focus is given that the friction-induced formation of interfacial bonding plays a critical role in the wear of frictional systems at atomic-scale.